HSV Serologic Testing for Pregnant Women: Willingness to Be Tested and Factors Affecting Testing - David A. Baker; Andrea Pressley; Lillian Meek; Reinaldo Figueroa; Barbara Yates; Lynn Dix (Hindawi Limited, 2011)
Objective. This prospective study was undertaken to evaluate pregnant women's willingness to undergo HSV type-specific serologic testing and factors affecting willingness in an obstetrics/gynecology ambulatory unit. Methods. At prenatal Visit 1, pregnant women (n=303) with no history of HSV-2 were tested for HSV-1/HSV-2 before and after they received counseling on genital and neonatal herpes. Results. In both the Unwilling Subgroup and the group that changed from being willing to being unwilling, the most common reasons for choosing not to be tested were not being at risk for genital herpes, being tested is too personal, and concern about what will be done with the results. Of the 134 participants in the Willing/Tested Subgroup, 27 (20%) were HSV-2 seropositive and 81 (60%) were HSV-1 seropositive. Conclusions. These results support the feasibility of HSV serologic testing and counseling in pregnant women.